Dissecting the Role of Leucine Zippers in the Binding of bZIP Domains of Jun Transcription Factor to DNA - Seldeen, Kenneth L. (2010)
Leucine zippers, structural motifs typically comprised of five successive heptads of amino acids with a signature leucine at every seventh position, play a central role in the dimerization of bZIP family of transcription factors and their subsequent binding to the DNA promoter regions of target genes. Herein, using analytical laser scattering (ALS) in combination with isothermal titration calorimetry (ITC), we study the effect of successive C-terminal truncation of leucine zippers on the dimerization and energetics of binding of bZIP domains of Jun transcription factor to its DNA response element. Our data show that all five heptads are critical for the dimerization of bZIP domains and that the successive C-terminal truncation of residues leading up to each signature leucine significantly compromises the binding of bZIP domains to DNA. Taken together, our study provides novel insights into the energetic contributions of leucine zippers to the binding of bZIP domains of Jun transcription factor to DNA.